LEVERAGING COMPETITIVE INTELLIGENCE PROCESSES IN SHIPPING INDUSTRY OPERATIONS AND STRATEGY - Anastasios-Nikolaos KANELLOPOULOS (Romanian Intelligence Studies Review)
The present paper explores the role of Competitive Intelligence (CI) within the Shipping industry, focusing on strategic information gathering and analysis for decision-making and strategic planning. The study synthesizes insights from scholarly works and academic perspectives to highlight the transformative impact of CI practices on operational efficiency and competitiveness in shipping operations. Key themes include the integration of CI technology, such as Business Intelligence (BI) tools and data analytics, to optimize decision-making processes and enhance service quality in a dynamic global market. The research also underscores the significance of diverse intelligence sources, including industry associations, government agencies, financial data providers, and academic research, in shaping CI strategies for Shipping companies. Furthermore, the discussion emphasizes the convergence of CI with geopolitical and macroeconomic analyses to inform strategic decision-making and mitigate operational risks. Overall, the paper contributes to a comprehensive understanding of CI practices and their implications for sustainable growth and resilience within the Shipping industry.